CONTEXT CLUES AND READING COMPREHENSION IN THE IBDP ENGLISH ACQUISITION EXAMINATION: ANALYZING TEXT DESIGN AND DISTRIBUTION - Ariyanti, Ariyanti; Hidayat, Didin Nuruddin; Husna, Nida (Linguists : Journal of Linguistics and Language Teaching, 2025)
While previous studies have extensively examined the effectiveness of using context clues in reading comprehension through experimental designs, limited attention has been given to the use of context clues in the reading section as an element of the examination, particularly in the context of the International Baccalaureate Diploma Programme (IBDP) English Acquisition Examination in 2023. This research examines the critical role of context clues in enhancing reading comprehension, specifically within the reading section of the English Acquisition component of the International Baccalaureate Diploma Programme (IBDP). Through a detailed analysis of context clues across three provided texts, the findings reveal a significant disparity in their distribution. The first text employs a wide range of context clues, such as definitions, punctuation, restatements, antonyms, cause and effect relationships, hints from surrounding sentences, and word formation. In contrast, the second and third texts depend on a narrower selection of context clues, which could hinder readers' capacity to understand intricate passages and fully appreciate subtle meanings. The research suggests that future studies should explore how different distributions of context clues impact specific learner outcomes and comprehension strategies, ultimately contributing to best practices in text design for educational assessments.